Implementation considerations for a point-of-care Neisseria gonorrhoeae rapid diagnostic test at primary healthcare level in South Africa: a qualitative study - Lindsey de Vos; Joseph Daniels; Avuyonke Gebengu; Laura Mazzola; Birgitta Gleeson; Benjamin Blümel; Jérémie Piton; Mandisa Mdingi; Ranjana M.S. Gigi; Cecilia Ferreyra; Jeffrey D. Klausner; Remco P.H. Peters (BMC Health Services Research, 2024)
Abstract Background South Africa maintains an integrated health system where syndromic management of sexually transmitted infections (STI) is the standard of care. An estimated 2 million cases of Neisseria gonorrhoeae (N. gonorrhoeae) occur in South Africa every year. Point-of-care diagnostic tests (POCT) may address existing STI control limitations such as overtreatment and missed cases. Subsequently, a rapid lateral flow assay with fluorescence-based detection (NG-LFA) with a prototype reader was developed for N. gonorrhoeae detection showing excellent performance and high usability; however, a better understanding is needed for device implementation and integration into clinics. Methods A qualitative, time-series assessment using 66 in-depth interviews was conducted among 25 trained healthcare workers involved in the implementation of the NG-LFA. Findings were informed by the Normalization Process Theory (NPT) as per relevant contextual (strategic intentions, adaptive execution, and negotiation capacity) and procedural constructs (coherence, cognitive participation, collective action, reflexive monitoring) to examine device implementation within primary healthcare levels. Interviews were audio-recorded, transcribed, and then analyzed using a thematic approach guided by NPT to interpret results. Results Overall, healthcare workers agreed that STI POCT could guide better STI clinical decision-making, with consideration for clinic integration such as space constraints, patient flow, and workload. Perceived NG-LFA benefits included enhanced patient receptivity and STI knowledge. Further, healthcare workers reflected on the suitability of the NG-LFA given current limitations with integrated primary care. Recommendations included sufficient STI education, and appropriate departments for first points of entry for STI screening. Conclusions The collective action and participation by healthcare workers in the implementation of the NG-LFA revealed adaptive execution within the current facility environment including team compositions, facility-staff receptivity, and STI management experiences. User experiences support future clinic service integration, highlighting the importance of further assessing patient-provider communication for STI care, organizational readiness, and identification of relevant departments for STI screening.